Recovery of Lithium Ions From Salt Lakes Using Nanofibers Containing Zeolite Carriers - Ding, Tao; Zheng, Mianping; Peng, Suping; Nie, Zhen; Lin, Yuhan; Wu, Qian (Frontiers in Energy Research, 2022)
Lithium is a key strategic metal in the 21st century and an important raw material in the new energy sector. With rapid growth of the market demand for lithium, the high-efficient extraction of lithium resources is of important economic significance. Taking zeolite as the carrier and using chemical grafting and electrospinning technologies, a kind of nanofiber containing crown ether (CE) was synthesized to adsorb Li(I) from the salt lake brine. This realizes the selective adsorption of Li(I) while retaining specific vacancies of epoxy groups in CE. The adsorption mechanism of nanofibers containing zeolite carriers and CE for Li(I) was revealed by the use of Fourier transform infrared (FT-IR) spectrometry, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT). The results show that after dsp3 hybridization of the outer orbit (2s) of Li(I), outer electrons on the nanofibers containing zeolite carriers and CE mainly migrate to the orbit for coordination with Li(I) thereat, thus realizing the capture of Li(I). The novel adsorbing material can reach adsorption equilibrium within 2.5 h and the adsorption kinetics for Li(I) conforms to the pseudo-second-order model and a maximum adsorption capacity of 8.6 mg/g. It can be found that the correlation coefficient fitted by Langmuir adsorption isotherm model is closer to 1, and the calculated maximum adsorption capacity is closer to the adsorption capacity obtained experimentally, therefore, it can be concluded that the adsorption process is more consistent with the Langmuir adsorption isotherm model, and the adsorption process can be regarded as monolayer adsorption. The adsorption capacity remains at 7.8 mg/g after 5 adsorption–desorption cycles, showing favorable stability and a strong ability to be regenerated. The research provides insights into the adsorption and recovery of Li(I) from the salt lake brine.